Nonvanishing of derivatives of Hecke L-functions associated to cusp forms inside the critical strip - Kohnen, Winfried; Sengupta, Jyoti; Weigel, Miriam (The Ramanujan journal, 2020)
The aim of this paper is to prove a nonvanishing result for derivatives of L-functions inside the critical strip analogous to Kohnen (J Number Theory 67:182-189, 1997).